Shared Decision-Making in Growth Hormone Therapy—Implications for Patient Care - Acerini, Carlo L.; Segal, David; Criseno, Sherwin; Takasawa, Kei; Nedjatian, Navid; Röhrich, Sebastian; Maghnie, Mohamad (Frontiers in Endocrinology, 2018)
Several studies have shown that adherence to growth hormone therapy (GHT) is not optimal. There are several reasons why patients may not fully adhere to their treatment regimen and this may have implications on treatment success, patient outcomes and healthcare spending and resourcing. A change in healthcare practices, from a physician paternalistic to a more patient autonomous approach to healthcare, has encouraged a greater onus on a shared decision-making (SDM) process whereby patients are actively encouraged to participate in their own healthcare decisions. There is growing evidence to suggest that SDM may facilitate patient adherence to GHT and in doing so, improve treatment outcomes. Whilst SDM is widely regarded as a healthcare imperative, there is little guidance on how it should be best implemented. Despite this, there are many opportunities for the implementation of SDM during the treatment journey of a patient with a GH-related disorder including but not limited to selecting the GH product. Barriers to the successful practice of SDM within the clinic may include poor patient education surrounding their condition and treatment options, limited healthcare professional time, lack of support from clinics to use SDM and healthcare resourcing restrictions. Here we discuss the opportunities for the implementation of SDM and the barriers that challenge its effective use within the clinic. We also review some of the potential solutions to overcome these challenges that may prove key to effective patient participation in treatment decisions. Encouraging a sense of empowerment for patients will ultimately enhance treatment adherence and improve clinical outcomes in GHT.